Penguatan Administrasi dan Tata Kelola Desa Berbasis New Public Service di Desa Tanjung Baru Kecamatan Indralaya Utara Kabupaten Ogan Ilir Provinsi Sumatera Selatan - Lionardo, Andries; Kurniawan, Rudy; Adam, Ryan (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
The practice of public administration in the life of the nation, state and society faces various obstacles that cause the implementation of service and welfare functions to be stalled. Strengthening Village Administration and Governance, especially in Tanjung Baru Village, North Indralaya District, Ogan Ilir Regency, South Sumatra Province, requires the quality of public services, which can be interpreted by comparing the views between the services received and the expectations of the services expected by the village community. In this connection, the poor bureaucratic service is no stranger to seeing and listening, and many formulations have been submitted for the implementation of government in the village. The New Public Service-Based Village Administration and Governance Strengthening Service is aimed at mapping the main problems faced in relation to public services. The method of implementing the activity is through joint lectures, student field practice and research conducted by observation techniques, literature studies and interviews with village officials and the community. Success in terms of public services cannot be separated from the level of understanding of vision between village officers related to their field of duty. Because improving the quality of human resources (HR) always gets priority as part of increasing employee development commitments. In conclusion, by including employees in village priority scale programs and training on the basics of village administration, leadership and the implementation of adaptive organizations are expected to increase village officials' mastery of good public service concepts.